346O Association of BAP1 with ATR protein and their clinical significance with patient outcome in uveal melanoma. (24th November 2019) - Jha, J; Pushker, N; Singh, M K; Singh, L; Sen, S; Kaur, J; Kashyap, S
Abstract: Background: Uveal melanoma (UM) is an intraocular malignancy commonly arising from the choroid. There is a lack of effective therapy to detect and treat early metastatic spread in these patients. Therefore, it is important to find new biomarkers that help in early detection of metastasis. ATR is localized at position 23 on the same chromosome 3 where BAP1 is located at position 21.1. Loss of BAP1 is a known poor prognostic marker of uveal melanoma. There is no current study available on UM with respect to ATR protein that induces DNA damage response. Therefore, the aim of the study is to detect the expression of ATR protein in the UM patients and correlate its expression with BAP1 loss. Methods: Expression of nuclear ATR was investigated on sixty-nine UM patients which were divided into two groups on the basis of BAP1 expression. Formalin-fixed paraffin embedded choroidal melanoma samples were taken to evaluate the expression of ATM and BAP1 by immunohistochemistry and validated by semi-quantitative PCR. Results were then correlated with clinicopathological parameters. To determine the prognostic significance, Kaplan–Meier and multivariate analysis were performed. Results: Patients with BAP1 loss also showed ATR loss in 62% of the cases which was statistically significant with high tumor pigmentation, LTD >10mm and cell type. At transcription level, down-regulation of ATR gene was found in 45% of cases and these results were in line with the IHC results. On multivariate analysis, advanced tumor staging and loss of ATR protein found to be independent prognostic factors. Conclusions: Our study emphasized the fact that loss of ATR could be a potential biomarker to detect the early metastasis in uveal melanoma. Hence, it could have a key role for therapeutic purpose. However, further studies are required in a larger cohort of patients with longer follow up and translational validation needs to be performed. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.